Did the time frame associated with the implementation of the Patient Protection and Affordable Care Act noticeably impact consumer bankruptcy filings?. Issue 12 (4th December 2017) - Hackney, Donald D.; Friesner, Daniel; Johnson, Erica H.
Abstract : Purpose: The purpose of this paper is to examine whether the timing associated with the implementation of the health insurance-related provisions of the Patient Protection and Affordable Care Act (ACA) altered the presence and distribution of medical/non-medical debts accumulated by different types of bankruptcy filers. Design/methodology/approach: Data were drawn from the US Bankruptcy Court's Eastern Washington District over the years 2009, 2011 and 2014 using interval random sampling. Binary probit and Tobit analyses were used to model the existence, and distribution, of medical debts and total debts, respectively, at the time of filing. The impact of the time frame associated with the ACA was operationalized via a Chow test for structural dynamic change. Findings: Chapter 13 filers in 2014 (post-ACA-based health exchange implementation) were more likely to report medical debts than Chapter 7 filers in the pre-intervention period, and were also more likely to report a larger proportion of outstanding debts owed to a single creditor. Filers claiming health insurance premium expenses in 2011 were (at the 10 percent significance level) more likely to report a more skewed distribution of medical debts. Originality/value: The time frame associated with the implementation of the ACA impacts the distribution of medical debts among filers who have sufficient net disposable income to fund a Chapter 13 plan. The polarization of outstanding medical debts may indicate coverage gaps in existing health insurance policies, whose costs would be disproportionately borne by patients operating on thin financial margins.